La Prédication existentielle dans les langues naturelles : valeurs et repérages, structures et modalités - Bottineau, Tatiana (TransAireS, 2020)
The articles in this collection deal with the expression of existential values in several languages of the world. The diversity of theoretical approach taken by the authors illustrates richness and universality of this problem, and demonstrates the similarities and the differences of its expression in natural languages. The original aspect of the collection is not only due to the description of possessive, locative or attributive values in several languages, but mainly due to the diversity of theoretical approaches to its analysis. The authors also study the evolution and interdependency of existential constructions. The existential predication may be presented as a specific operation of locating one term relative to another, expressed by the means of a non-canonical marking of constituents, a non-canonical constituent order within the utterance, and by using a particular existential marker. Typological analysis or a simple comparison between two singular languages, an enunciative approach or a study of the forms complete each other and open up new perspectives for linguistic research on the expression of existence in natural languages of the world.